Analysis system of the water management complex in Ukraine and the search for ways to improve - Зацерковний, В.І.; Плічко, Л.В. (Science-based technologies, 2017)
The analysis of problems related to water resources management, which should be taken changing water management system in favor of sustainable development and implementing the requirements of The Water Framework Directive, has been carried out. The basic principles of management and control in water use are given. The model of realization of actions on the decision of water management and ecological problems in the basin water-economic complex is presented. Increasing the ecological and economic efficiency of water use will help to establish a balance between satisfying the needs of the population and the sectors of the economy, limiting their use and reducing the burden on nature.